The Visual Artists Awards 1997-98. - Burden, Chris; Divola, John; Gamblin, Noriko; Halper, Vicki; Hershman, Lynn; Ireland, David; Marioni, Tom; Moseley, Alexander; Moseley, Jaylene; Nagle, Ron; Purifoy, Noah; Rubins, Nancy; et al. (Pasadena : Flintridge Foundation, 1998)
Burden, Chris ; Divola, John ; Hershman, Lynn ; Ireland, David ; Marioni, Tom ; Nagle, Ron ; Purifoy, Noah ; Rubins, Nancy ; Saar, Betye ; Thompson, Mark ; Villa, Carlos ; Wong, Al
biografie, bibliografie
The book is published on the occasion of the inauguration of the Flintridge Foundation Visual Artists Awards.
Engels
boek